Medical conscience clause and the hard case - Rzymkowska, Katarzyna (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
The aim of the paper is to describe the situation of using the medical conscience clause as a hard case in Ronald Dworkin’s understanding. Like in a hard case, the clause creates a possibility to appeal to an autonomous system of rules in case of an unjust result of interpretation of the rules of law. It is so because the doctor’s situation is individual and specific in contrast to the rules of law. Moreover, the clause has to be seen as a way to resolve a hard case, not as its reason. Furthermore, the institution of the conscience clause imposes additional duties on doctors, which are motivated by judging legal principles against one another. Additionally, the Dworkin’s interpretative attitude allows extending the category of hard cases to non-judicial cases and not adjudicated by judges.